Guardians of Rural Heritage: Exploring Residents’ Attitudes towards the Inheritance of Intangible Cultural Heritage in Chinese Traditional Villages - Shen, Huaheng; Yu, Lingyun; Fadzila Aziz, Nor; Peng, Li; Long, Yufeng; Luo, Yu; Xiang, Xiaokang (New Countryside, 2025)
As pivotal agents in traditional villages, residents play a crucial role in the preservation and continuation of intangible cultural heritage within these villages. Grounded in the theory of planned behaviour, this study examines residents’ attitudes toward the inheritance of intangible cultural heritage in traditional Chinese villages, using Zhaoxing Dong Village as a case study. To explore these attitudes in depth and from multiple dimensions„ the research collected questionnaire data from 246 village residents. Analytical methods, including Pearson correlation coefficients and mediation effect tests, were employed to investigate the relationships between residents’ perceptions, their willingness to inherit, their actual inheritance behaviors, and demographic differences. The findings indicated that residents generally exhibited positive attitudes regarding cultural heritage inheritance; however, their actual inheritance behaviors were relatively low. A significant positive correlation was observed among residents’ perceptions of cultural inheritance, their inheritance willingness, and actual inheritance actions, with perceptions exerting a strong positive influence on actual behaviours. This willingness to inherit also partially mediated this relationship, underscoring its crucial role in translating perceptions into actions. Moreover, factors such as age, educational background, and length of residence were significantly associated with residents’ inheritance perceptions and behaviours. Finally, specific policy and practice recommendations are proposed to promote residents’ broader, deeper, and more active engagement in the inheritance and safeguarding of intangible cultural heritage.